GANGGUAN KEPRIBADIAN NARSISTIK TOKOH UTAMA NOVEL LADY SUSAN KARYA JANE AUSTEN - Evi Irawanti Saragih (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
Lady Susan is a novel by Jane Austen which published very first time in 1871 with an epistolary style of writing. This novel tells the story about Susan Vernon, the main character who has just lost her husband forever. Although Susan Vernon became a single parent, but her beauty and charm cannot be doubted. She is used to living a luxurious life and full of wealth. This causes her self-confidence high and then do everything to survive include married her daughter Frederica to the man of her choice and then looking for a rich man for herself. This study seeks to explain how the confidence of Susan Vernon leads to narcissistic personality disorder. The data source is novel Lady Susan which will be explain based on personality theory by Sigmund Freud. The results of the discussion showed that Lady Susan has a narcissistic personality disorder caused when her parents and environment spoiled her too much. The urge to fulfill desires in any way carried over into adulthood. This disorder not only affects those closest to patient but also has a bad impact on the sufferer because it demands to be perfect in order to get praise and respect. Patients will get a negative response because their desires tend to be unreasonable. When experience a failure, they lost a confidence and finally being embarrassed to appear in front of public.